2013
DOI: 10.3164/jcbn.12-86
|View full text |Cite
|
Sign up to set email alerts
|

The effects of <i>n</i>-3 polyunsaturated fatty acid-rich total parenteral nutrition on neutrophil apoptosis in a rat endotoxemia

Abstract: Although recruited neutrophils function as first-line defense to remove bacteria, delayed apoptosis is implicated in persistent inflammation leading to organ injury. Leukotrien B4, n-6 polyunsaturated fatty acids (PUFAs) product, is one of the mediators that delay neutrophil apoptosis. The mechanism of the beneficial effects of supplementation of fish oil-based long-chain n-3 PUFAs in parenteral nutrition for critically ill patients has not been fully understood. One possible mechanism is the less inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…( 12 ) We previously demonstrated that n -3 PUFA-rich PN regulated neutrophil apoptosis and prevented synthesis of pro-inflammatory eicosanoids, partially explaining the protective effects seen in the clinical setting. ( 33 ) Our results are also consistent with previous studies suggesting that utilizing fish oil to partly replace soybean oil in PN may both decrease the amount of linoleic acid and increase the amount of biologically-active n -3 PUFA. In clinical studies of patients with sepsis who were intolerant of EN and received PN with either standard soybean oil-based emulsion or an emulsion containing fish oil, blood leukocyte counts and serum C-reactive protein concentrations were lower and production of LTB 5 by stimulated neutrophils was much higher in patients receiving fish oil.…”
Section: Discussionsupporting
confidence: 92%
“…( 12 ) We previously demonstrated that n -3 PUFA-rich PN regulated neutrophil apoptosis and prevented synthesis of pro-inflammatory eicosanoids, partially explaining the protective effects seen in the clinical setting. ( 33 ) Our results are also consistent with previous studies suggesting that utilizing fish oil to partly replace soybean oil in PN may both decrease the amount of linoleic acid and increase the amount of biologically-active n -3 PUFA. In clinical studies of patients with sepsis who were intolerant of EN and received PN with either standard soybean oil-based emulsion or an emulsion containing fish oil, blood leukocyte counts and serum C-reactive protein concentrations were lower and production of LTB 5 by stimulated neutrophils was much higher in patients receiving fish oil.…”
Section: Discussionsupporting
confidence: 92%
“…More recently, in a rat model of sepsis, Terashima et al . [ 69 ] demonstrated that FO-enriched PN may regulate neutrophil functions, restoring delayed apoptosis, which was associated with an increase in leukotriene B5 (LTB5) production from peritoneal neutrophils. Hecker et al .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, n ‐3 PUFAs have a series of beneficial effects on mammalian cells, which can inhibit allergic reactions, cancer, and a series of cellular lesions . Studies have shown that n ‐3 PUFAs can protect the mitochondrial membrane integrity, maintain mitochondrial activity, improve cell activity through adjusted K + channel activity and PI3K/Akt signaling pathway, and inhibit cell apoptosis . High concentrations of n ‐3 PUFAs can be adjusted by the second messenger to promote cell proliferation.…”
Section: Discussionmentioning
confidence: 99%